COMPLEX TARGET PROGRAM AS A TOOL TO STIMULATE REGIONAL DEVELOPMENT - Азарова, Анжелика; Ткачук, Людмила; Каплун, Ирина (Public Administration Issues, 2019)
The article focuses on the development of a new conceptual approach to public management of regional development through constructing and implementing an appropriate automated complex goal program (CGP). The purpose of the article is to justify a new approach to public management of regional development in the context of deepening European integration processes. The current study exploits the method  of goal assessment of alternatives for building a hierarchy of goals for the complex goal program of regional development public management.The investigation is based on the analysis of legislative acts of Ukraine, European strategies “Digital Agenda of Europe”, “Europe 2020: a strategy of reasonable, sustainable and comprehensive growth”, development strategies of various regions of Ukraine, presented on their websites; expert data processed in the CGP; sociostatistical base of economic advantages development of various regions of Ukraine. Having carried out the analysis, the authors identified the advantages and disadvantages of various theories of regional development management; justified the concept of regional development by designing an automated complex goal program; defined the set of optimal projects that contribute to the improvement of regional development with the help of proposed CGP. Developed CGP allows allocating limited financial resources rationally to optimum projects. Automation of the CGP was done with modern IT technologies such as the decision support system “Solon-2”. The research results can be applied in the regions that need to optimize the system of public management of regional development. The results of the study might enhance the distribution of limited financial resources between identified priority projects and their sub-goals which can significantly improve the process of public administration of the region.